Fecal elimination of fluralaner in different carnivore species after oral administration - Berny, Philippe Jacques; Belhadj, Dalil; España, Bernadette; Lécu, Alexis (Frontiers in Veterinary Science, 2024)
Fluralaner is a recent external parasiticide, first of a new class of drugs (isoxazoline parasiticides). It is widely used in companion animals both for its wide spectrum (fleas, ticks and other mites) but also for its ease of use (oral tablets given once for 1 to three months). It is known to be eliminated primarily via the feces (>90%) as the unchanged compound. In zoo carnivores, controlling external parasites is also important and there are no specific products with a marketing authorization to control them. The first objective of this study was to evaluate the pharmacokinetic profile of fluralaner in zoo carnivores. After adjusting the oral dose using allometric equations, animals were dosed and fecal samples were collected on a regular basis for up to three months to determine the fecal elimination curve of fluralaner as a surrogate of plasma kinetics (for ethical and safety reasons, plasma samples were not considered). The second objective was to demonstrate that fluralaner can be eliminated over a prolonged period of time, thereby raising questions about its potential impact on non-target species such as arthropods. Our results show that, despite limitations and a limited number of animals included, most carnivores eliminate fluralaner in their feces for several weeks to months (in Lions, fluralaner was still detectable after 89 days). To our knowledge, this is the first study demonstrating such a long elimination period in animals. Further studies would be required to investigate the risk associated with the presence of active residues in other carnivore feces for the environment, especially in dogs and cats, considering the large use of this class of compounds.